Exploring matric art students’ interpretation of the art curriculum and the socio-political implications of the topic issue at three independent schools in Gauteng - Swanepoel, Cheree (Stellenbosch : Stellenbosch University, 2016)
Thesis (MA)--Stellenbosch University, 2016.